avant-garde - Konstantin Lidin (Проект Байкал, 2019)
Avant-garde is a military term. It is an advanced detachment of the army, which is the first to face the enemy, the first to get into action, and which is more likely to die than others. The destinies of avant-garde movements at the turn of the 20th century are full of tragic episodes and biographies. How should we treat the historical heritage of the avant-garde of the 20th century? Should we be respectful toward its memory in the hope that the new avant-garde waves would be treated more carefully? Or should we search for the keys in the history of avant-garde to understand today’s and tomorrow’s problems of stylistic development of art? The selection of articles in the AVANT-GARDE section includes not only the materials on the history of architecture, but also articles on book graphics of the avant-garde (for its time) modern style, and still poorly studied episodes of the formation of the Siberian style and painting tradition.